LANGUAGE INTERFERENCE ON ENGLISH: [n] ARTICULATION OF INDONESIAN STUDENTS - Susiati, Susiati; Laila, Malikatul; Maskuroh, Qanitah (Kajian Linguistik dan Sastra, 2010)
Being familiar in âtahsinâ rule in Arabic may have influenced ones in pronouncing regressive assimilation [n] in English. The study aims to identify the similarities and differences between English and Arabic with âtahsinâ rules based onthe place of articulation and to describe how the students of Muâallimat programpronounce regressive assimilation [n] in English. The data collected are the English speech produced by the students of Muâallimat program in PONPES AlMukmin Ngruki Sukoharjo having âtahsinâ background, especially English consonants and regressive assimilation [n] and Arabic ânun sakinahâ law in âtahsinârules. The data are analyzed by technique of comparing Arabic and English viewedfrom rules on phonetic base. The results show that (1) the similarities and differences between English consonant sounds and Arabic with âtahsinâ rules lies in itsplace of articulation; and (2) the students of Muâallimat program belonging tokhalaqoh tahsinul qurâan have not always pronounced English regressive assimilation [n]better than those who donât belong to khalaqoh tahsinul qurâan.Key words: interference, regressive assimilation, tahsin.